2024
DOI: 10.3390/ph17060670
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Polyphenols, Plant Metabolites, and Allergic Disorders: A Comprehensive Review

Mohd Farhan,
Asim Rizvi,
Mohammad Aatif
et al.

Abstract: Given the ongoing rise in the occurrence of allergic disorders, alterations in dietary patterns have been proposed as a possible factor contributing to the emergence and progression of these conditions. Currently, there is a significant focus on the development of dietary therapies that utilize natural compounds possessing anti-allergy properties. Dietary polyphenols and plant metabolites have been intensively researched due to their well-documented anti-inflammatory, antioxidant, and immunomodulatory characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 281 publications
0
0
0
Order By: Relevance
“…Polyphenols, due to their natural origin, are generally believed to be non-toxic and safe. Data from clinical and preclinical studies demonstrated that the evaluated phenolic compounds were well tolerated, free of adverse effects and had a high safety profile [ 139 , 140 ]. However, this cannot be established as a rule.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Polyphenols, due to their natural origin, are generally believed to be non-toxic and safe. Data from clinical and preclinical studies demonstrated that the evaluated phenolic compounds were well tolerated, free of adverse effects and had a high safety profile [ 139 , 140 ]. However, this cannot be established as a rule.…”
Section: Conclusion and Perspectivementioning
confidence: 99%